Rosuvastatin‐Induced Carotid Plaque Regression in Patients With Inflammatory Joint Diseases: The Rosuvastatin in Rheumatoid Arthritis, Ankylosing Spondylitis and Other Inflammatory Joint Diseases Study. Issue 7 (July 2015) - Rollefstad, S.; Ikdahl, E.; Hisdal, J.; Olsen, I. C.; Holme, I.; Hammer, H. B.; Smerud, K. T.; Kitas, G. D.; Pedersen, T. R.; Kvien, T. K.; Semb, A. G.
<x xml:space="preserve">Abstract</x> Objective Patients with rheumatoid arthritis (RA) and carotid artery plaques have an increased risk of acute coronary syndromes. Statin treatment with the goal of achieving a low‐density lipoprotein (LDL) cholesterol level of ≤1.8 mmoles/liter (≤70 mg/dl) is recommended for individuals in the general population who have carotid plaques. The aim of the ROsuvastatin in Rheumatoid Arthritis, Ankylosing Spondylitis and other inflammatory joint diseases (RORA‐AS) study was to evaluate the effect of 18 months of intensive lipid‐lowering treatment with rosuvastatin with regard to change in carotid plaque height. Methods Eighty‐six patients (60.5% of whom were female) with carotid plaques and inflammatory joint disease (55 with RA, 21 with AS, and 10 with psoriatic arthritis) were treated with rosuvastatin to obtain the LDL cholesterol goal. Carotid plaque height was evaluated by B‐mode ultrasonography. Results The mean ± SD age of the patients was 60.8 ± 8.5 years, and the median compliance with rosuvastatin treatment was 97.9% (interquartile range [IQR] 96.0–99.4). At baseline, the median number and height of the carotid plaques were 1.0 (range 1–8) and 1.80 mm (IQR 1.60–2.10), respectively. The mean ± SD change in carotid plaque height after 18 months of treatment with rosuvastatin was −0.19 ± 0.35 mm (P < 0.0001). The mean ± SD baseline LDL cholesterol level was 4.0 ± 0.9 mmoles/liter (154.7 ± 34.8 mg/dl), and the mean reduction in the LDL cholesterol level was −2.3 mmoles/liter (95% confidence interval [95% CI] −2.48, −2.15) (−88.9 mg/dl [95% CI −95.9, −83.1]). The mean ± SD LDL cholesterol level during the 18 months of rosuvastatin treatment was 1.7 ± 0.4 mmoles/liter (area under the curve). After adjustment for age/sex/blood pressure, no linear relationship between a reduction in carotid plaque height and the level of LDL cholesterol exposure during the study period was observed. Attainment of the LDL cholesterol goal of ≤1.8 mmoles/liter (≤70 mg/dl) or the amount of change in the LDL cholesterol level during the study period did not influence the degree of carotid plaque height reduction. Conclusion Intensive lipid‐lowering treatment with rosuvastatin induced atherosclerotic regression and reduced the LDL cholesterol level significantly in patients with inflammatory joint disease.